A Catheter-Related Bloodstream Infection Caused by the Yeast Kodamaea ohmeri - CH, Ding; MN, Tzar; S, Biswas; NAS, Muttaqillah; AA, Wahab (IIUM Medical Journal Malaysia, 2020)
Catheter-related bloodstream infections caused by Kodamaea ohmeri are generally not considered due to the relative scarcity of reported cases. This is a case of an 85-year-old man with poorly controlled diabetes mellitus who was initially admitted to our hospital for diabetic ketoacidosis. An internal jugular catheter was inserted as part of the initial management. A week later the patient developed a temperature spike and a yeast identified as Kodamaea ohmeri by ID 32 C (bioMérieux, France) was isolated from both his central and peripheral blood cultures. The catheter was removed and the patient was treated with fluconazole despite the organism’s relatively high minimum inhibitory concentration (2 μg/mL) to this antifungal. The fungemia resolved following a 2-weeks course of fluconazole.